A bibliometric analysis study on sport sciences: trends and recommendations for athletes` performance - Fredianto, M.; Ulfa, M.; Khairunnisa, R. A.; Chilmi, M. Z. (International Journal of Kinesiology & Sports Science, 2024)
Background Sports science is responsible for locating, approving, developing, and perfecting various strategies to improve athletic performance. New methods for assessing an athlete`s technical and physical prowess are being created daily, and fresh training concepts are evolving impressively swiftly. If coaches had access to the most up-to-date techniques and knowledge to create the most effective training plans, athletes would gain significantly. This study aims to find patterns and make recommendations to stakeholders to enhance athlete performance.